Distribution of heavy metals in roadside dust of Petaling Jaya, Malaysia with multivariate and correlation analyses for source identification. Issue 2 (26th January 2021) - Shabanda, Ibrahim Sani; Koki, Isa Baba; Raof, Siti Farhana Abdul; Lee, Yook Heng; Mainal, Azizah; Abu Bakar, Nor Kartini; Khor, Sook Mei
ABSTRACT: Anthropogenic emission is on the increase in urban cities due to increased human activities. However, the pollution level of heavy metals in urban environments due to emission from various anthropogenic sources could attain toxic levels to humans and biota. The roadside dust collected from Petaling Jaya, Malaysia was analysed for Pb, Cr, Cu, Cd, As, Ni, and Fe by using ZEE nit 650 P Graphite furnace atomic absorption spectroscopy. The contamination levels of these metals were assessed in terms of the geoaccumulation index (Igeo), enrichment factor (EF), contamination factor (Cf), and integrated pollution index (IPI). The result of the principal component analysis (PCA) and hierarchical cluster analysis (HCA) revealed that the variations found in different concentrations of heavy metals were mainly due to industrial and traffic emissions. The computed results of Igeo and EF of heavy metals in urban dust suggested that there were pollutions of Cd, Cu, Pb, and As. Meanwhile, Igeo and EF of Ni, Cr, and Fe were very low and posed no serious pollution. The Cf and IPI assessments also indicated that Cd, Cu, and Pb were the major pollutants in Petaling Jaya urban dust. On the other hand, the potential ecological risks for single element (Er) confirmed the IPI results and the potential ecological risk index (RI) indicated that generally, the degree of pollution of heavy metals in roadside dust of PJ was considerable. These results could help in the development of suitable management strategies to minimise pollution by using various remediation methods in Petaling Jaya.